Ethnobotanical importance, phytochemical constituents, and pharmacological properties of Withania somnifera - Nurul Bariah Jamalludin; Nurhuda Manshoor (Shahrekord University of Medical Sciences, 2022)
Withania somnifera belongs to the family of Solanaceae. It is widely used by the locals, especially in India, as a medicinal plant. W. somnifera is rich in alkaloid and steroidal lactone that account for various pharmacological activities. The present study aimed to review all the evidence on the ethnobotanical perspective of W. somnifera in some countries. This review also analyses the bioactive compounds that account for the pharmacological activities. The online medical literature databases such as ScienceDirect, PubMed, and Google Scholar were used to search articles up to March 2022. W. somnifera is widely used in Asian and African countries like India and South Africa, Pakistan, Egypt, Jordan, and Lesotho. In India, W. somnifera is prepared by boiling and crushing the leaves and roots to make a tonic poultice, juice, and paste to treat bacterial infections and bruises. Numerous in vivo and in vitro studies have demonstrated that W. somnifera exerts pharmacological effects such as anti-Parkinson's, anti-Alzheimer's, cardioprotective, antidiabetic, antiarthritic, and antibacterial properties. Withaferin A and withanolide are the major bioactive compounds contributing to the pharmacological effects. W. somnifera is a valuable plant that has been used in traditional medicine systems for a long time and is supported by its wide range of pharmacological activities. The extensive medicinal uses of W. somnifera are a sign of its great potential.